2013
DOI: 10.1177/1090820x13478819
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Perspective of Complication Rates for Elective Nonreconstructive Breast Surgery: An Analysis of NSQIP Data From 2006 to 2010

Abstract: Elective breast surgery is a safe procedure with an extremely low incidence of life-threatening complications and mortality. Comprehensive data collated from the NSQIP initiative add to the literature, and the findings of this multi-institutional study may help further guide patient education and expectations on potentially deleterious outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…Furthermore, the UR rate for breast reconstruction by tissue expander (CPT 19357) alone was 5.8%, weighing heavily on the overall UR rate. The most commonly performed procedure in this study was reduction mammaplasty with an overall UR rate of 1.2%, in agreement with previously reported re-operation rates [23]. Despite these minor differences, the 1.9% UR rate remains acceptably low compared to the rates reported across all specialties (0.6-11%) [1][2][3][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the UR rate for breast reconstruction by tissue expander (CPT 19357) alone was 5.8%, weighing heavily on the overall UR rate. The most commonly performed procedure in this study was reduction mammaplasty with an overall UR rate of 1.2%, in agreement with previously reported re-operation rates [23]. Despite these minor differences, the 1.9% UR rate remains acceptably low compared to the rates reported across all specialties (0.6-11%) [1][2][3][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 89%
“…Rates of complications as reported in the literature are highly variable, ranging from 1% to 38%, depending on the definition. 34,3640 Similar to our transfeminine cohort, the most common complication in the cisgender group was reoperation secondary to hematoma formation, occurring in 0.8% of patients. This finding is consistent with retrospective studies from Handel 58 and Araco, 36 that reported hematoma formation in 1%–2% of patients.…”
Section: Discussionsupporting
confidence: 59%
“…Breast augmentation is a relatively safe procedure. In a recent study of 725 patients who underwent augmentation, the overall complication rate was less than 1.5 percent and life-threatening complications were exceedingly rare (3). Of more utility in this patient population, is the evaluation of changes in quality of life, body image, patient satisfaction and self-esteem.…”
Section: Introductionmentioning
confidence: 99%